Molecular Characterization and Risk Factors of Giardia duodenalis among School Children from La Habana, Cuba - Luis Enrique Jerez Puebla; Fidel A. Núñez; Isabel Martínez Silva; Lázara Rojas Rivero; Marta Martínez González; Yuliet Méndez Sutil; Lucía Ayllón Valdés; Iraís Atencio Millán; Norbert Müller (Journal of Parasitology Research)
Giardia duodenalis is considered the most common protozoan infecting humans worldwide. Molecular characterization of G. duodenalis isolates has revealed the existence of eight groups (assemblages A to H) which differ in their host distribution. A cross-sectional study was conducted in 639 children from La Habana between January and December 2013. Two assemblage-specific PCRs were carried out for the molecular characterization. The overall prevalence of Giardia infection was 11.9%. DNA from 63 of 76 (82.9%) samples was successfully amplified by PCR-tpi, while 58 from 76 (76.3%) were detected by PCRE1-HF. Similar results by both PCRs were obtained in 54 from 76 samples (71%). According to these analyses, assemblage B and mixed assemblages A + B account for most of the Giardia infections in the cohort of children tested. Our current study identified assemblage B as predominant genotype in children infected with Giardia. Univariate analysis indicated that omission of washing hands before eating and keeping dogs at home were significant risk factors for a Giardia infection. In the future, novel molecular tools for a better discrimination of assemblages at the subassemblages level are needed to verify possible correlations between Giardia genotypes and symptomatology of giardiasis.